Mulch requirements for erosion control with the no-till system in the tropics: a review - Lal, R. (1984)
Accelerated soil erosion is one of the factors responsible for rapid decline in crop yield on arable lands in the tropics even within a few years of deforestation and new land development. Engineering practices of water runoff management are expensive to install and their effectiveness depends on regular maintenance. Research in West Africa and elsewhere in the tropics has indicated the potential of biological control measures associated with mulch farming techniques and of no-till system in reducing runoff and soil erosion to within tolerable limits. The magnitude of soil loss reduction and of water conservation produced by the notill system, however, depends on the quantity and durability of the crop residue mulch. The" mulch factor" also depends on slope gradient, on soil erodibility and hydrological properties, and on crop characteristics. Biological control measures and crop residue mulches influence runoff and soil erosion directly by preventing drop impact, and indirectly by improving hydrological properties through their effects on soil structure, moisture regime, and water transmission properties. For slopes ranging between 2 and 20%, mulch rates of 6-8 t ha-1 have been found to be adequate if regularly maintained. The effective mulch rate to control soil erosion was generally less with the no-till than with conventional methods of seed-bed preparation. Mulch rate was also les's for crops that develop a rapid canopy cover c lose to the soil surface. Results from the tropics are reviewed in terms of their implications for soil and crop management systems.